Spatio-temporal Variation Characteristics and Influencing Factors of Bank Collapse in Reservoir Area of Jinghong Hydropower Station - LIANG Ruifeng; XU Peng (Renmin Zhujiang)
The reservoir area of Jinghong hydropower station belongs to the medium mountain canyon landform with variable stratum lithologies and complex geological structures.By investigation and review of bank collapse in the reservoir area in 2009,2012,2014 and 2019,this paper summarizes and analyzes the temporal-spatial variation characteristics and influencing factors of bank collapse.The results show that:①Up to the survey period in 2019,there are 299 bank collapses in the reservoir area.The bank collapse with volume between 10~100 m3 occupies the first place,130 bank collapses stop developing and 169 bank collapses are developing;②The number of bank collapse is increasing year by year;the bank collapses are mainly distributed in the reservoir section with steep terrain,thicker loose layer and strong weathered rock;the reservoir area is mainly characterized by small-scale bank collapse,but there is a trend of gradual expansion;the increase of bank collapses which are developing is obviously slowing down and the bank collapses in earlier stage show a gradually stable state;③Specific topography,thicker loose layer,economic trees which are unfavorable to soil and water conservation,and frequent human production activities are the main factors for bank collapses.